Digital Entrepreneurship and Innovation in Central America - International Finance Corporation (World Bank, Washington, DC, 2022)
Coronavirus disease 2019 (COVID-19) has made the digital revolution more important than ever. A strong entrepreneurial ecosystem is essential for digital revolution. This report assesses entrepreneurship ecosystems in Central America and provides a series of recommendations. The assessment was carried out in four countries of Central America - Costa Rica, El Salvador, Guatemala, and Honduras - and combined a set of analytical instruments. It included an analysis of firm-level micro-data, an analysis of public programs and intermediary organizations to support entrepreneurship, focus groups, and an online survey of more than 2,000 firms on technology use. The findings and the corresponding recommendations also cover challenges that make it difficult for small and medium enterprises (SMEs) to digitalize their operations and for start-ups in general.